Membranes and processes for forward osmosis-based desalination : recent advances and future prospects - Wang, Yi-Ning (2020)
Forward osmosis (FO) is an increasingly important technology that has been deemed promising for addressing the global issue of water scarcity. Rapid progress over the past decade has been marked by significant innovations in the membrane development and process design. The key idea is to develop next-generation membranes through advanced membrane fabrication methods as well as hybrid systems where the FO process can really value-add. As such, this article provides an overview of the various FO membrane designs, in particular, the thin-film composite, surface-modified, and mixed matrix and biomimetic membranes. The pros and cons of each type of membranes are discussed together with the strategies used to optimize membrane properties such as structural parameter (S), water permeability (A) and salt permeability (B) to achieve enhanced FO performances. Furthermore, we also discuss the roles of FO in the various hybrid systems and evaluate the potential of these hybrid systems for desalination. Lastly, we provide our perspectives, especially in the area of membrane fabrications and FO hybrid systems, to shed light on the future research directions for harnessing the true potential of FO for desalination.